The Impact of Teacher Innovation Expectations on Blended Learning Usage Behavior : Usage Intention as a Mediator - Gao , Zheng; XU, Ping (Journal of Roi Kaensarn Academi, 2023)
This study explores the mediating role of teachers' intention to use blended teaching mode between teachers' performance expectations and usage behavior. We used the teacher's use intention scale, teacher's use behavior scale, and performance expectation scale to construct the structural equation model and the research hypothesis equation model. The three scales have been revised by experts and confirmatory analysis, and have good reliability and validity. and fit. Electronic questionnaires were distributed to six colleges and universities in Jilin Province, China using scientific and valid scales, and 889 valid questionnaires were finally recovered. The analysis results show that teachers' performance expectation is a positive predictor of usage behavior, and usage intention plays a partial mediating role between usage behavior and performance expectation. Therefore, improving teachers' performance expectations can improve teachers' use behavior of blended teaching mode. At the same time, it is concluded that performance expectations have a positive impact on usage behavior through usage intentions. Schools should promote the use of blended teaching models by increasing intention to use.